2013
DOI: 10.2460/javma.243.1.120
|View full text |Cite
|
Sign up to set email alerts
|

Injection of platelet- and leukocyte-rich plasma at the junction of the proximal sesamoid bone and the suspensory ligament branch for treatment of yearling Thoroughbreds with proximal sesamoid bone inflammation and associated suspensory ligament branch desmitis

Abstract: Although PRP-treated horses were more likely to start a race during the 2-year-old racing year versus control group horses, results for horses in each group were not significantly different for the 3- and 4-year-old racing years. Therefore, the PRP treatment protocol evaluated in this study did not seem to improve future racing performance of yearling Thoroughbreds with proximal sesamoid bone inflammation and associated SLB desmitis, compared with injection of saline solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(67 citation statements)
references
References 18 publications
3
62
2
Order By: Relevance
“…From the 60 clinical studies included in this review, 11 (18.3%) [ 18 - 28 ] were conducted in horses, and 49 (81.7%) [ 29 - 77 ] were conducted in humans. Considering both species together, the results of the clinical trials were evenly distributed, that is, beneficial effects were observed in 28 studies (46.7%) [ 19 , 21 - 23 , 25 , 26 , 28 , 29 , 32 , 34 - 36 , 38 , 39 , 41 , 49 , 55 , 57 , 58 , 62 , 64 , 69 , 70 , 72 - 76 ], and negative effects were observed in 26 studies (43.3%) [ 18 , 30 , 31 , 33 , 37 , 42 - 45 , 47 , 48 , 50 - 54 , 56 , 59 , 60 , 63 , 65 - 68 , 71 , 77 ] after PRP application (Additional file 1 : Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…From the 60 clinical studies included in this review, 11 (18.3%) [ 18 - 28 ] were conducted in horses, and 49 (81.7%) [ 29 - 77 ] were conducted in humans. Considering both species together, the results of the clinical trials were evenly distributed, that is, beneficial effects were observed in 28 studies (46.7%) [ 19 , 21 - 23 , 25 , 26 , 28 , 29 , 32 , 34 - 36 , 38 , 39 , 41 , 49 , 55 , 57 , 58 , 62 , 64 , 69 , 70 , 72 - 76 ], and negative effects were observed in 26 studies (43.3%) [ 18 , 30 , 31 , 33 , 37 , 42 - 45 , 47 , 48 , 50 - 54 , 56 , 59 , 60 , 63 , 65 - 68 , 71 , 77 ] after PRP application (Additional file 1 : Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Earnings may also be heavily influenced by tactics [5,6]. Furthermore, earnings normally decline with age as younger animals have age-restricted race entry opportunities and supplemented purses [15,23,24], and sex has a strong influence, with entire males having increased potential earnings levels due to their worth to the TB breeding industry [13,14]. Consideration of the advantages of the commonly used outcome measures identified that no measure was ideal, with the highest scoring measures only achieving around half of the 15 specified criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Although the cost of training and upkeep probably results in withdrawal of less able horses from training and racing [5], it has been reported that 38% of horses starting 9-15 races in the UK have never previously won [11] and it is postulated that a bad racehorse may even be run more often to help it 'learn its job' [12]. Number of starts may well also vary with the owner or trainer's intentions for the horse, age at the time of the intervention, and sexwith males, especially geldings, being more frequently kept in race training for longer than reproductively valuable fillies [13,14]. Data regarding number of starts are easy to collate, and studies should be encouraged to report number of starts over a defined period of time to facilitate comparative work.…”
Section: Discussionmentioning
confidence: 99%
“…Two‐year‐old horses treated with PRP were more likely to start a race than horses treated with saline, but their earnings were similar. Additionally, some PRP‐treated horses developed cosmetic blemishes at the injection site . Interleukin‐1 receptor antagonist protein (IRAP; Dechra, Dusseldorf, Germany) and IRAP II (Arthrex, Bonita Springs, Florida, USA). Comparing the response to PRP and bone marrow aspirate in vitro , a recent study using tenocytes cultured from SDFTs showed that both bone marrow aspirate and PRP derived by plasma centrifugation (ACP; Arthrex, Bonita Springs, Florida, USA) stimulated secreted collagen production more than other commercial PRP devices, IRAP and IRAP II, and plasma.…”
Section: New Treatments: Research Evidence To Guide Selection Of Biolmentioning
confidence: 99%